Localization of the limit set of trajectories of the Euler-Bernoulli equation with control - Zuev, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate a differential equation in a Hilbert space that describes vibrations of the Euler-Bernoulli elastic beam with feedback control. The relative compactness of positive semitrajectories of the considered equation is proved. Constructing a Lyapunov functional in explicit form and using the invariance principle, we obtain representations of limit sets.